Paradoxo entre o depósito pecuniário recursal e o acesso das microempresas ao duplo grau de jurisdição trabalhista - Rocha, Rubervan Dantas da (2010)
In life you can be faced with injustice and, in face of that, cannot remain inert, that something can be done to rebuild the injustice witnessed. If you do not have legitimacy before the courts of justice, not being a legitimate party to the cause, at least there is the space of the legal academy to discuss and reflect about it, in order to sow the seeds in the world of teaching. The current system of appeals of labor court sentences requires employers to make cash deposits as a requirement of admissibility to the second level of jurisdiction. Would all employers be able to bear this burden? Wouldn t such a requirement be a barrier to access to justice, in particular, to the two levels of jurisdiction? And unalienable duty of the State to secure access to justice? Access to the Judiciary Labor rules was created in a historical context to justify the thesis of the hipossuficiency employee before the employer, and it was, and still is, currently, under certain conditions. The theory of the hipossuficiency employee resulted in a polarized view of the procedural relationship, where one side is the other employee and the employer, but it was forgotten that among the employers are the differences of their own, thus resulting in a pseudo-equality of the pole passive demand. The Federal Constitution of 1988 brought the supremacy of the guiding principles as part of the whole system of positive law, among them one can highlight the principles of equality, legality, unalienable of due process, the two levels of jurisdiction, the broad defense, adversarial, which will be the subject of this study. Before a monocratic trial or even collegiate trial, factors such as human fallibility (s) of judge (s) and lack of satisfaction of both parties with the jurisdiction that was provided, which are subjective assumptions constitute the review of decisions by a court 1st or 2nd instance, gives the citizen the right to return their case to the Judiciary. If under certain perspective there is the need for quick and effective judicial assistance, for another, there is sometimes a misuse of the legal instrument by lawyers, creating a pro-dilatory culture, resulting in iconoclasm of the judiciary. The principle of equality represents that equals should be treated equally and those different should be treated in different ways. Thus, all employers would be equal in their economic and social conditions? Is it just to stipulate that the review of decisions unfavorable labor small business assumption goal, as the appeal bond, which implies availability and undocking immediate monetary value of companies with monthly turnover up to R$ 20.000,00? This study has no intention of exhausting the theme, but tries to consider the importance of reflecting, on the basis of constitutional principles, the possible inaccessibility of appeals by the labor enterprises, due to the enforceability of the appeal deposit